ANALISIS PERKEMBANGAN KREDIT USAHA RAKYAT DI KECAMATAN DEWANTARA SEBELUM DAN PADA MASA PANDEMI COVID-19 - Maisyuri; Muttaqien; keumala, cut muftia; Rizal, Syamsul (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2022)
This study aims to analyze the development of People's Business Credit in Dewantara District before the Covid-19 pandemic and during the Covid-19 pandemic, and analyze the comparison of the development of People's Business Credit in Dewantara District before the Covid-19 pandemic with the development of People's Business Credit during the pandemic. Covid-19. Secondary data on the development of People's Business Credit in Dewantara District before and during the Covid-19 pandemic in the form of data on the number of distribution of People's Business Credit and data on the number of recipients of People's Business Credit in 2019 and 2020. The results show that: Development of People's Business Credit in the District Dewantara before the Covid-19 pandemic tended to be stable in terms of KUR recipients and KUR distribution with the development of People's Business Credit in Dewantara District during the Covid-19 pandemic, but the development of People's Business Credit in Dewantara District before the Covid-19 pandemic was better than during the pandemic Covid-19, where the development of People's Business Credit in the Dewantara District before the Covid-19 pandemic with the Covid-19 pandemic, there was no significant difference